2014
DOI: 10.1172/jci44071
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle–derived stem/progenitor cells promote functional murine peripheral nerve regeneration

Abstract: Peripheral nerve injuries and neuropathies lead to profound functional deficits. Here, we have demonstrated that muscle-derived stem/progenitor cells (MDSPCs) isolated from adult human skeletal muscle (hMDSPCs) can adopt neuronal and glial phenotypes in vitro and ameliorate a critical-sized sciatic nerve injury and its associated defects in a murine model. Transplanted hMDSPCs surrounded the axonal growth cone, while hMDSPCs infiltrating the regenerating nerve differentiated into myelinating Schwann cells. Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 79 publications
(84 reference statements)
3
68
0
1
Order By: Relevance
“…If compared, their results of approximately 450 axons recovered in the ruptured sciatic nerve and 50% retention of downstream muscle mass are apparently less than the values of the non-cell transplanted media control group in the present study. Nonetheless, previous and present studies have collectively demonstrated that skeletal muscles are important and practical cell sources for nerve repair [9, 1517]. Similarly, several human adult somatic stem cell lines, such as human hair follicle stem cells [22], human umbilical cord-derived mesenchymal stem cells [23], and human bone marrow stromal cells [24], have been applied to the regeneration of damaged peripheral nerves, and their cellular differentiation capacities have been examined in vivo .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…If compared, their results of approximately 450 axons recovered in the ruptured sciatic nerve and 50% retention of downstream muscle mass are apparently less than the values of the non-cell transplanted media control group in the present study. Nonetheless, previous and present studies have collectively demonstrated that skeletal muscles are important and practical cell sources for nerve repair [9, 1517]. Similarly, several human adult somatic stem cell lines, such as human hair follicle stem cells [22], human umbilical cord-derived mesenchymal stem cells [23], and human bone marrow stromal cells [24], have been applied to the regeneration of damaged peripheral nerves, and their cellular differentiation capacities have been examined in vivo .…”
Section: Discussionmentioning
confidence: 88%
“…Another group has reported similar differentiation and therapeutic capacity using human muscle-derived stem cells [15]. The isolated cells demonstrated neuronal and glial phenotypes in vitro and ameliorated a critical-sized sciatic nerve injury after in vivo transplantation into the SCID mouse model, showing differentiation into Schwann cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Various types of transplanted stem cells were shown to enhance peripheral nerve regeneration in preclinical animal studies of nerve reconstruction. A variety of cell types, such as bone marrow stromal cells, adipose-derived stromal cells, muscle-derived stem cells, and dental pulp stem cells, were applied to this approach [17][18][19][20][21][22][23][24]. However, recent studies have reported low transplanted stem cell survival rates.…”
mentioning
confidence: 99%
“…Больше того, было установлено, что эффективным может быть даже ксеногенный клеточный материал. Введение мышам человече-ских прекьюсорных клеток обусловливало развитие у подопытных животных регенерации аксонов при участии донорских клеток [20].…”
Section: о пластичности ск ее значении для организма и о механизмах unclassified